2020
DOI: 10.1021/acs.chemmater.0c01151
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Site Engineering for Creating Unusual Red Emission in La3Si6N11:Ce3+

Abstract: Traditionally, phosphors are developed by doping activators on standard crystallographic sites of selected inorganic hosts, thus enabling the prediction of their luminescence with some empirical models or theoretical calculations. Here, we propose the idea of interstitial site engineering as a totally different way to design phosphors with promising properties. In detail, a red-emitting phosphor La3Si6N11:Ce3+,Al3+ was developed by engineering the interstitial Ce3+ site, which produces an unusual red emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 50 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…In the recent study, Xie's group also developed a red-emitting phosphor La 3 Si 6 N 11 : Ce 3+ , Al 3+ with promising properties by aliovalent substitution of Si 4+ by Al 3+ ions. 73 When the Al 3+ ions are incorporated into the Si 4+ crystallographic site of the host structure, Ce 3+ as an interstitial ion prefers to occupy the void of the [Si 8 N 8 ] ring (Figure 7e) in La 3 Si 6 N 11 for the charge compensation that causes the aliovalent substitution. As a result, these La 3 Si 6 N 11 :Ce 3+ , Al 3+ phosphors display an unusual red emission band centering at 600−665 nm with different Al 3+ concentrations (Figure 7f) and show great potential for improving the optical quality.…”
Section: Emission Manipulation Of Doped Activators Via Substitution S...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent study, Xie's group also developed a red-emitting phosphor La 3 Si 6 N 11 : Ce 3+ , Al 3+ with promising properties by aliovalent substitution of Si 4+ by Al 3+ ions. 73 When the Al 3+ ions are incorporated into the Si 4+ crystallographic site of the host structure, Ce 3+ as an interstitial ion prefers to occupy the void of the [Si 8 N 8 ] ring (Figure 7e) in La 3 Si 6 N 11 for the charge compensation that causes the aliovalent substitution. As a result, these La 3 Si 6 N 11 :Ce 3+ , Al 3+ phosphors display an unusual red emission band centering at 600−665 nm with different Al 3+ concentrations (Figure 7f) and show great potential for improving the optical quality.…”
Section: Emission Manipulation Of Doped Activators Via Substitution S...mentioning
confidence: 99%
“…As a result, these La 3 Si 6 N 11 :Ce 3+ , Al 3+ phosphors display an unusual red emission band centering at 600−665 nm with different Al 3+ concentrations (Figure 7f) and show great potential for improving the optical quality. 73 To sum up, heterovalent (including aliovalent) substitution certainly will cause charge imbalance and give rise to various charge compensation mechanisms. To give a sharp insight into the connection between these mechanisms and local structure as well as luminescence properties can arouse many other inspirations to design new phosphor materials.…”
Section: Emission Manipulation Of Doped Activators Via Substitution S...mentioning
confidence: 99%
“…Moreover, our group developed a general heterovalent substitution strategy by Ln 3+ (Ln = Gd, Tb, Dy, Tm, Yb, and Lu) substituting Hf 4+ in K 2 HfSi 3 O 9 :Eu 2+ and realized the results of “kill three birds with one stone” with controllable emission properties, improved thermal stability and high quantum efficiency . Recently, Xie’s group also discovered an unusual red emission in La 3 Si 6 N 11 :Ce 3+ via the heterovalent substitution of Si 4+ by Al 3+ ions to create an interstitial Ce 3+ site . Hence, the heterovalent substitution strategy can really open a new avenue for the PL tuning.…”
Section: Design Principles To Tune the 4f–5d Transition Of Eu2+mentioning
confidence: 99%
“…These include AlN:Eu 2+ , 43),44) ¢-sialon;Eu 2+ , 26),45), 46) (La,Ca) 3 Si 6 N 11 :Eu 2+ , 47) and La 3 (Si,Al) 6 N 11 :Ce 3+ . 48) The position of Eu 2+ in ¢-sialon remained a miracle until Kimoto et al directly observed it by using high angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). 45) As seen in Figs.…”
Section: Structure-property Relationsmentioning
confidence: 99%
“…Xie et al observed a large redshift in Al-doped La 3 Si 6 N 11 :Ce 3+ , producing a broadband red phosphor ( em = 665 nm, fwhm ³200 nm). 48) With aids of the first principles calculations, the red emission can be ascribed to that Ce 3+ occupies the interstitial sites (i.e., [Si8N8] voids) newly formed as a charge compensator for the aliovalent substitution of Si 4+ by Al 3+ .…”
Section: Structure-property Relationsmentioning
confidence: 99%